Low Carbohydrate Diets for Diabetic Cardiomyopathy: A Hypothesis - Kleissl-Muir, Sabine; Rasmussen, Bodil; Owen, Alice; Zinn, Caryn; Driscoll, Andrea (Frontiers in Nutrition, 2022)
Elevated blood glucose levels, insulin resistance (IR) and hyperinsulinemia, the key aspects of type 2 diabetes mellitus (T2DM), contribute to the development of a certain form of cardiomyopathy. This cardiomyopathy, also known as diabetic cardiomyopathy (DMCM), typically occurs in the absence of overt coronary artery disease (CAD), hypertension or valvular disease. DMCM encompasses a variety of pathophysiological processes impacting the myocardium, hence increasing the risk for heart failure (HF) and significantly worsening outcomes in this population. Low fat (LF), calorie-restricted diets have been suggested as the preferred eating pattern for patients with HF. However, LF diets are naturally higher in carbohydrates (CHO). We argue that in an insulin resistant state, such as in DMCM, LF diets may worsen glycaemic control and promote further insulin resistance (IR), contributing to a physiological and functional decline in DMCM. We postulate that macronutrient modulation targeting hyperinsulinemia through CHO restriction may be able to improve tissue and systemic IR. In recent years low carbohydrate diets (LC) including ketogenic diets (KD), have emerged as a safe and effective tool for the management of various clinical conditions such as T2DM and other metabolic disorders. CHO restriction achieves sustained glycaemic control and successfully reverses IR. In addition to this, its pleiotropic effects may present a metabolic stress defence and facilitate improvement to cardiac function in patients with HF. We therefore hypothesise that patients who adopt a LC diet may utilise less medications and experience improvements in HF-related symptom burden.